2020
DOI: 10.22271/chemi.2020.v8.i4a.9810
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of dry cow therapy and internal teat sealant on intramammary infection during subsequent lactation

Abstract: In the present study cows were screened 75 th day before expected date of calving by using MCMT, somatic cell count and pH. Then positive cows for subclinical mastitis were randomly divided into four groups, each comprising of 8 cows. MCMT, SCC and pH evaluation were performed in milk samples of all the 32 cattle under therapy on day 0 pre-treatment (at drying off) and 7, 45 and 90 post treatment (after calving). The result revealed significant decrease in SCC and MCMT grading in all the treatment groups that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…The mean pH (7.12±0.06) values of mastitis affected goats increased significantly (p<0.01) as compared to healthy control (6.81±0.12) (Table 3). These findings were in accordance with Tomar et al (2018) [27] and Mohamed et al (2014) [12] who reported increased milk pH in mastitisaffected goats. Increased pH in clinical mastitis milk samples was due to increased udder inflammation and responsible for an increase in the mammary gland permeability to the blood components like bicarbonates and other alkaline salts into the milk, along with reduced production of lactose by the gland so that the milk pH became above 7.0 (Mohamed et al, 2014) [12] .…”
Section: Resultssupporting
confidence: 92%
“…The mean pH (7.12±0.06) values of mastitis affected goats increased significantly (p<0.01) as compared to healthy control (6.81±0.12) (Table 3). These findings were in accordance with Tomar et al (2018) [27] and Mohamed et al (2014) [12] who reported increased milk pH in mastitisaffected goats. Increased pH in clinical mastitis milk samples was due to increased udder inflammation and responsible for an increase in the mammary gland permeability to the blood components like bicarbonates and other alkaline salts into the milk, along with reduced production of lactose by the gland so that the milk pH became above 7.0 (Mohamed et al, 2014) [12] .…”
Section: Resultssupporting
confidence: 92%